Body Weight–Supported Treadmill Training Is No Better Than Overground Training for Individuals with Chronic Stroke: A Randomized Controlled Trial. Issue 6 (November 2014) - Middleton, Addie; Merlo-Rains, Angela; Peters, Denise M.; Greene, Jennifaye V.; Blanck, Erika L.; Moran, Robert; Fritz, Stacy L.
Abstract : Background: Body weight-supported treadmill training (BWSTT) has produced mixed results compared with other therapeutic techniques.Objective: The purpose of this study was to determine whether an intensive intervention (intensive mobility training) including BWSTT provides superior gait, balance, and mobility outcomes compared with a similar intervention with overground gait training in place of BWSTT.Methods: Forty-three individuals with chronic stroke (mean [ SD ] age, 61.5 [13.5] years; mean [ SD ] time since stroke, 3.3 [3.8] years), were randomized to a treatment (BWSTT, n = 23) or control (overground gait training, n = 20) group. Treatment consisted of 1 hour of gait training; 1 hour of balance activities; and 1 hour of strength, range of motion, and coordination for 10 consecutive weekdays (30 hours). Assessments (step length differential, self-selected and fast walking speed, 6-minute walk test, Berg Balance Scale [BBS], Dynamic Gait Index [DGI], Activities-specific Balance Confidence [ABC] scale, single limb stance, Timed Up and Go [TUG], Fugl-Meyer [FM], and perceived recovery [PR]) were conducted before, immediately after, and 3 months after intervention.Results: No significant differences (α = 0.05) were found between groups after training or at follow-up; therefore, groups were combined for remaining analyses. Significant differences (α = 0.05) were found pretest to posttest for fast walking speed, BBS, DGI, ABC, TUG, FM, and PR. DGI, ABC, TUG, and PR results remained significant at follow-up. Effect sizes were small to moderate in the direction of improvement.Conclusions: Future studies should investigate the effectiveness of intensive interventions of durations greater than 10 days for improving gait, balance, and mobility in individuals with chronic stroke.